2001
DOI: 10.1038/35094067
|View full text |Cite
|
Sign up to set email alerts
|

APC, Signal transduction and genetic instability in colorectal cancer

Abstract: Colorectal cancer arises through a gradual series of histological changes, each of which is accompanied by a specific genetic alteration. In general, an intestinal cell needs to comply with two essential requirements to develop into a cancer: it must acquire selective advantage to allow for the initial clonal expansion, and genetic instability to allow for multiple hits in other genes that are responsible for tumour progression and malignant transformation. Inactivation of APC--the gene responsible for most ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
702
3
23

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 827 publications
(749 citation statements)
references
References 134 publications
17
702
3
23
Order By: Relevance
“…Accumulating evidence indicates that activation of Wnt/β-catenin signaling is one of the direct causes of gastric and intestinal tumor development [4][5][6][7] . It has been shown that the expression of several Sox family genes, including Sox2, Sox9 and Sox17 are induced by Wnt/β-catenin signaling 31,33,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that activation of Wnt/β-catenin signaling is one of the direct causes of gastric and intestinal tumor development [4][5][6][7] . It has been shown that the expression of several Sox family genes, including Sox2, Sox9 and Sox17 are induced by Wnt/β-catenin signaling 31,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…This canonical Wnt signaling (Wnt/β-catenin signaling) plays a key role in the maintenance of intestinal stem cells and progenitor cells 2,3 . Moreover, the constitutive activation of Wnt/β-catenin signaling causes gastrointestinal tumorigenesis in both human 4,5 and mice 6,7 . It has also been shown that β-catenin accumulation, a hallmark of Wnt activation, is particularly enhanced in the invasion front and metastasized colon cancer cells, suggesting that promotion of Wnt/β-catenin signaling is important for malignant progression 8 .…”
Section: Introductionmentioning
confidence: 99%
“…::11q23-411qter) [16]/46,XY [4] (Figure 1a). The deletion of APC in 5q22.2 was confirmed by FISH (Figure 1b), which in an infant with Gardner fibroma was highly suggestive of a second hit in the context of a constitutional APC variant.…”
Section: Resultsmentioning
confidence: 99%
“…2,3 When the APC function is lost, b-catenin accumulates and migrates to the nucleus, affecting proliferation, differentiation, migration, and apoptosis. 4 Fibromatous soft tissue lesions, including desmoid-type fibromatosis and Gardner fibroma, may occur sporadically or as part of FAP. 1,[5][6][7] The FAP-associated fibromatous soft tissue lesions often present b-catenin overexpression, which may result from activating somatic variants of the CTNNB1 gene (encoding the b-catenin) or from biallelic inactivation of the APC gene.…”
Section: Introductionmentioning
confidence: 99%
“…En présence de WNT, le récepteur Frizzled, associé à une protéine apparentée au récepteur des lipoprotéines de basse densité (LRP6), est activé. S'ensuit une cascade d'événements peu documentée au cours de laquelle l'inhibiteur de GSK-3β GBP est activé via Dishevelled (pour plus de détails, voir [38]). En consé-quence, la caténine β n'est plus dégradée, diffuse dans le noyau, déplace Groucho et active la transcription sous le contrôle de LEF/Tcf.…”
Section: Atpunclassified